A dual design thinking – universal design approach to catalyze neurodiversity advocacy through collaboration among high-schoolers - Schuck, Rachel K.; Fung, Lawrence K. (Frontiers in Psychiatry, 2024)
Introduction Neurodiversity describes the fact that humans all have different brains with unique qualities that contribute to society. Though understanding of neurodiversity is gaining traction among the general public, there remains considerable stigma and prejudice toward neurodiverse people. One way to combat these issues is to teach individuals about neurodiversity and encourage them to develop advocacy skills. Development of such knowledge is especially important for adolescents, as they have the capacity to make small (e.g., interpersonal interactions) and large (e.g., school-wide) impacts. Methods Eighty-nine high schoolers participated in a two-week virtual summer camp in 2022; research consent/assent was obtained from 19 (11 neurodiverse/neurodivergent). Campers learned about neurodiversity, Universal Design for Learning (UDL), and Design Thinking (DT) through lectures from researchers and neurodivergent people, as well as group activities and discussions. Campers worked in small groups to design a neurodiversity advocacy project based on the principles of UDL and DT. Each group was facilitated by camp counselors–some of whom were neurodiverse–who were all committed to neurodiversity advocacy. Participants completed questionnaires about autism, ADHD, and dyslexia pre- and post-camp. Some also completed optional post-camp interviews. Results Pre-camp stigma toward neurodiverse conditions was generally low. However, autism stigma was significantly higher than dyslexia stigma (Z = −2.24, p = 0.025). After camp, autism stigma decreased (Z = −2.98, p = 0.003;) and autism [t(13) = 3.17, p = 0.007] and ADHD [t(13) = 2.87, p = 0.013] knowledge improved. There were no significant changes in ADHD or dyslexia stigma or dyslexia knowledge. Participants reported enjoying collaborating with other campers and learning about UDL and DT. Thematic analysis of interviews generated four themes: Increased Understanding of Neurodiversity; Increasing Empathy and Becoming Less Judgmental; Creating a Neurodiverse Community; and More Awareness is Needed. Discussion This pilot investigation suggests that a virtual summer camp can be effective in improving attitudes toward and knowledge of neurodiversity. Qualitative analysis indicated participants became more accepting after the camp, both in terms of being less judgmental toward neurodiverse people and more self-accepting among neurodivergent campers. Future research should investigate the long-term effects of such a program, particularly with diverse samples of students.